PENGARUH KOMUNIKASI MELALUI GRUP WHATSAPP UNTUK MENINGKATKAN KINERJA KARYAWAN DI PT. SMARTPHONE LENOVO MEDAN - Elisabeth Sitepu; Novi Juli Yanti Sagala (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This research was conducted to see the effect of communication through Whatsapp groups to improve employee’s performance at PT. Smartphone Lenovo Medan. The approach applied in quantitative descriptive research. The sampling technique used is total sampling with a sample of 49 people. The research carried out shows that communication that occurs in the form of messages or information sent can arrive quickly without having to convey it to several people, but by notifying it in the company's whatsapp group all employees can read and find out the information provided so that they quickly get good results within the company. The existing performance of employees at PT. The Lenovo Medan smartphone is getting better because it is more helpful by using the whatsapp group. There is the influence of communication through the whatsapp group to improve the performance of employees at PT. The Lenovo Medan smartphone is 0.627, which means that the relationship is quite significant with the WhatsApp application because its use is very helpful in the process of delivering messages between employees, especially employees who have groups in it, making it easier to deliver messages.